Laparo-endoscopic management of chole-choledocholithiasis: Rendezvous or intraoperative ERCP? A single tertiary care center experience - Lagouvardou, Elpiniki; Martines, Gennaro; Tomasicchio, Giovanni; Laforgia, Rita; Pezzolla, Angela; Caputi Iambrenghi, Onofrio (Frontiers in Surgery, 2022)
Introduction: The management of chole-choledocholithiasis remains a matter of debate, to preserve minimal invasive management, different options have been proposed, with single or two stage approach. Two techniques of single stage approach are intraoperative ERCP and Rendezvous that have the great advantage of reducing the length of hospital stay with increased patient’s compliance. The aim of this retrospective study was to evaluate and compare the efficacy and safety between intraoperative ERCP and Rendezvous technique during more than 15 years. Material and methods: Clinical records of 113 patients submitted to single stage management for chole-choledocholithiasis, between January 2003 and December 2020, were retrospectively reviewed using a prospectively maintained database. Patients were separated into those managed with intraoperative ERCP and those with Rendezvous and compared for their intra and postoperative parameters. All patients were followed-up for 6 months in outpatient setting .Results: Sixty-eight (60%) patients were treated with Intraoperative ERCP and remaining 45 (40%) with rendezvous. There were no significant differences in terms of comorbidities. ERCP was performed with a median operative time of 145 min (104-168) with an endoscopic time of 27 min (15-36). Meanwhile, rendezvous was performed with a significant lower operative (120 min (94-147)) and endoscopic time (15 min (12-22)). No intraoperative complications were recorded. Patients treated with Rendezvous had a significantly lower median hospitality stay (4(3-5) vs 3 (2-4) days, p<0.05). No hospital readmission at 30 days or mortality were observed in both groups. Ten mild pancreatitis cases were observed, mainly in intraoperative ERCP group (9 vs 1, p<0.05), all treated conservatively. Only two patients treated with intraoperative ERCP developed later biliary complications. Conclusions: Laparoscopic rendezvous should be considered a preferable alternative to intraoperative ERCP for the treatment of patients with concomitant CBD stones and gallstone.